Reinforcement Effect of Inclined Prestressed Concrete Pipe Piles on an Inclined Soft Foundation - De-quan Zhou; Chen-xi Feng; Liu-xi Li; Yi Zhou; Qin Zhu (Advances in Civil Engineering)
The embankment slope is vulnerable to slip and collapse, when prestressed concrete pipe (PCP) piles are used to reinforce the inclined soft foundation to bear the load of the embankment. Accordingly, this study puts forward new programs for strengthening embankment foundation with inclined, rather than vertical, PCP piles. Based on an actual engineering accident with embankment slope collapse, this study establishes a finite element model, accompanied by analysis of engineering characteristics and reinforcement effects of the foundation. The main conclusions are drawn as follows: (1) when a pile-supported foundation is used to strengthen the inclined soft foundation, PCP piles in the lower part of the embankment are subjected to bending moments, with their maximum value appearing in the upper part of the PCP pile at the embankment slope foot. During the embankment filling, the maximum pile bending moment may reach the ultimate bending load, resulting in bending failure accompanied with large lateral displacement and even slope collapse. The maximum horizontal displacement of the foundation is located at the foot of the embankment slope. (2) Reinforcement using inclined PCP piles contributes to smaller maximum pile body bending moments than that using vertical PCP piles and loading berms, and such contribution is enhanced when the inclination angle of PCP piles in the lower part of the slope gets larger. Therefore, inclined PCP piles with high angles are optimum in improving the overall stability of the foundation. (3) Compared with vertical PCP piles, inclined PCP piles contribute to smaller horizontal displacement and vertical settlement in foundation reinforcement, which means better reinforcement effects. Moreover, as the inclination angle of PCP piles increases, the maximum displacement decreases rapidly, associated with greatly enhanced lateral stability.